PERILAKU PENGGUNAAN ANTIBIOTIK TANPA RESEP DI APOTEK X DI KOTA PAYAKUMBUH SUMATERA BARAT - Yulia, Mega; Parsono, Ruddy; Armal, Khairil (Jurnal Riset Kefarmasian Indonesia, 2022)
Antibiotic are organic compounds produced by various species of microorganisms and are toxic to other species of microorganisms. Irrational use of antibiotic can lead to resistance. The problem of resistance in addition to having an impact on morbidity and morality also has a very high economic and social impact. Research has been done on the behavior of using antibiotic without a prescription at pharmacy x in Payakumbuh City. The purpose of this study was to determine the use of antibiotic without a doctor's prescription at pharmacy X in Payakumbuh City. This research is non-experimental with data analyzed included the level of awareness of the use of antibiotic. The study used a descriptive method with random or accidental sampling with data collection using a questionnaire with 100 samples from 5296 populations. The results showed that the most widely used antibiotics were amoxicillin (46%); the type of disease that most patients treated with antibiotics was toothache (33%); the most sources of information about antibiotics came from friends or family (35%); the reason most people use antibiotics without a doctor's prescription is that previous treatment has a satisfactory effect (36%) and the level of patient awareness of the use of antibiotics is still in the sufficient category (42%).